Study on Swine Brucellosis Infection Rate in the Avan Community of Aragatsotn Region - Sargsyan, M. A.; Balasanyan, H. S.; Tovmasyan, G. R. (ՀԱԱՀ հիմնադրամ)
Investigations on the swine brucellosis has been conducted for the first time within 2021-2022 throughout the recent 60 years. Probably, the infection carrier small and large cattle have become the cause of brucellosis infection. Joint housing and zoohygienic conditions, as well as the remnants of infected dairy products have served as predisposing factors for morbidity. Rose-Bengal test and agglutination reaction were used to detect antibodies in blood serum. As a result of epidemiological analysis, the indicators of morbidity and insecurity rates have amounted to 0.0025 (0.25 %), 0.0075 (0.75 %), respectively, while the economic damage has made AMD 1 mln 310 thousand. ,
Keywords: Veterinary Science and Animal Breeding